Endothelin-1 stimulates human monocytes in vitro to release TNF-α , IL-1β and IL-6 - E. Helset; T. Sildnes; R. Seljelid; Z.S. Konopski (Hindawi Limited, 1993)
Increased plasma- and tissue levels of endothelin-1 (ET-1) during inflammatory diseases, have suggested a role of ET-1 in the pathophysiology of inflammatory reactions. The authors have studied the effect of ET-1 on cytokine release from monocytes and monocyte-derived macrophages. ET-1 increased secretion of TNF-α, IL-1β and IL-6 in a dose- and time-dependent manner. Optimal ET-1 concentration ranged from 0.01 to 1 nM. The maximal response was a 200 to 400% increase in cytokine release. A time-course study revealed that the pattern of cytokines induced by ET-1 was different in monocytes and macrophages, although an early increase in TNF-α was observed in both monocyte and macrophage supernatants. In conclusion, ET-1 stimulates monocytes and macrophages to release cytokines thereby demonstrating a potential role for ET-1 in regulation of inflammatory responses.